spub-ri-2018-0052-File007 – Supplemental material for Does sports club participation contribute to physical activity among children and adolescents? A comparison across six European countries ... - Kokko, Sami; Martin, Leena; Geidne, Susanna; Hoye, Aurelie Van; Lane, Aoife; Meganck, Jeroen; Scheerder, Jeroen; Seghers, Jan; Villberg, Jari; Kudlacek, Michal; Badura, Petr; Mononen, Kaisu; et al. (SAGE Journals, 2018)
Supplemental material, spub-ri-2018-0052-File007 for Does sports club participation contribute to physical activity among children and adolescents? A comparison across six European countries by Sami Kokko, Leena Martin, Susanna Geidne, Aurelie Van Hoye, Aoife Lane, Jeroen Meganck, Jeroen Scheerder, Jan Seghers, Jari Villberg, Michal Kudlacek, Petr Badura, Kaisu Mononen, Minna Blomqvist, Bart De Clercq and Pasi Koski in Scandinavian Journal of Public Health ...